2006
DOI: 10.1007/s11837-006-0066-0
|View full text |Cite
|
Sign up to set email alerts
|

The oxidation of single-crystal nickel-based superalloys

Abstract: A phase transformation occurs in nickel-based single-crystal superalloys as a result of the oxidation that creates the external NiO scale. This transformation, which is the precursor to internal oxidation, creates the β phase (NiAl) fi rst followed by the δ phase (Ni 2 Al 3 ) prior to the formation of the spinel Ni (Cr,Al) 2 O 4 and Al 2 O 3 in succession. The implications of this effect on the rate of oxidation are discussed in this article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 21 publications
4
18
0
Order By: Relevance
“…13 suggests the presence of an Al-rich precipitate with the ratio of atom% of Ni and Al approximately equal to unity suggesting the formation of the β (NiAl) phase. Similar oxidation induced phase transformation and formation of different Al-rich precipitates are reported in the oxidation studies of CMSX-10 by Akhtar et al [48]. The XRD patterns from the grip and the gauge region of the unpolished samples creep tested at 982…”
Section: Metallographic and Chemical Analysissupporting
confidence: 81%
“…13 suggests the presence of an Al-rich precipitate with the ratio of atom% of Ni and Al approximately equal to unity suggesting the formation of the β (NiAl) phase. Similar oxidation induced phase transformation and formation of different Al-rich precipitates are reported in the oxidation studies of CMSX-10 by Akhtar et al [48]. The XRD patterns from the grip and the gauge region of the unpolished samples creep tested at 982…”
Section: Metallographic and Chemical Analysissupporting
confidence: 81%
“…Company [44]. The microstructural stability in these alloys involved control of TCP phases that could precipitate in moderate amounts over a long time at temperatures above 900°C, but were detrimental to mechanical properties such as fatigue and creep resistance [45].…”
Section: Physical Metallurgy Of Single Crystal N5mentioning
confidence: 99%
“…The visual appearance, thickness, and oxide type is influenced by the material composition. Several oxidation studies of SRR99 [29,30] and CMSX10K (variant of CMSX10N) are available, [30][31][32] which provide good insight into the oxidation behavior of these materials. However, the key aspects to be emphasized is that these studies were performed under atmospheric conditions and for prolonged isothermal holds.…”
Section: Subsequent Oxidation Of Metal Surface Detached From Mold mentioning
confidence: 99%
“…This result is unlike in isothermal oxidation studies where the thickness of the oxide was of the order of 10 lm. [29][30][31][32] In fact, previous investigations into the oxidation of fully solutioned SRR99 over the temperature range of 1073 K to 1273 K (800°C to 1000°C) report the formation of an external layer of predominantly (Ni, Co) O with a small amount of (Ni, Co) TiO 3 , beneath which various internal spinel phases occur followed by internally oxidized chromium oxide and alumina, with Al 2 O 3 being the layer next to the unoxidized substrate. [30] The presence of the external predominantly (Ni, Co) O scale in that study differs from the observations reported in this investigation.…”
Section: Subsequent Oxidation Of Metal Surface Detached From Mold mentioning
confidence: 99%